Proteomics identifies thymidine phosphorylase as a key regulator of the angiogenic potential of colony-forming units and endothelial progenitor cell cultures - Pula, Giordano; Mayr, Ursula; Evans, Colin; Prokopi, Marianna; Vara, Dina S; Yin, Xiaoke; Astroulakis, Zoe; Xiao, Qingzhong; Hill, Jonathan; Xu, Qingbo; Mayr, Manuel (My University, 2009)
Endothelial progenitor cell (EPC) cultures and colony-forming units (CFUs) have been extensively studied for their therapeutic and diagnostic potential. Recent data suggest a role for EPCs in the release of proangiogenic factors. To identify factors secreted by EPCs, conditioned medium from EPC cultures and CFUs was analyzed using a matrix-assisted laser desorption/ionization tandem time-of-flight mass spectrometer combined with offline peptide separation by nanoflow liquid chromatography. Results were verified by RT-PCR and multiplex cytokine assays and complemented by a cellular proteomic analysis of cultured EPCs and CFUs using difference in-gel electrophoresis. This extensive proteomic analysis revealed the presence of the proangiogenic factor thymidine phosphorylase (TP). Functional experiments demonstrated that inhibition of TP by 5-bromo-6-amino-uracil or gene silencing resulted in a significant increase in basal and oxidative stress-induced apoptosis, whereas supplementation with 2-deoxy-D-ribose-1-phosphate (dRP), the enzymatic product of TP, abrogated this effect. Moreover, dRP produced in EPC cultures stimulated endothelial cell migration in a paracrine manner, as demonstrated by gene-silencing experiments in transmigration and wound repair assays. RGD peptides and inhibitory antibodies to integrin alphavbeta3 attenuated the effect of conditioned medium from EPC cultures on endothelial migration. Finally, the effect of TP on angiogenesis was investigated by implantation of Matrigel plugs in mice. In these in vivo experiments, dRP strongly promoted neovascularization. Our data support the concept that EPCs exert their proangiogenic activity in a paracrine manner and demonstrate a key role of TP activity in their survival and proangiogenic potential.
Keywords: Angiogenesis; Endothelium; Progenitor cells; Proteomics; Vascular biology